Regulation of de novo lipogenesis and fatty acid desaturation in human adipocytes - Collins, J (2009)
De novo lipogenesis (DNL) in the human adipocyte is not fully understood. While some believe this to be an insignificant pathway, others have argued that adipose tissue may even be the main site of DNL. The enzyme stearoyl-CoA desaturase (SCD) plays a key role in the synthesis of monounsaturated fatty acids and its activity may be co-ordinately regulated with DNL. The recently-described Scdl knockout mouse model fuelled interest in this enzyme as a possible target for the treatment of obesity. Human preadipocytes were isolated from adipose tissue biopsy samples and differentiated in vitro for 14 days to produce adipocytes. Using stable isotopes, the main precursors for DNL in human adipocytes were determined, as was the regulation of DNL by an exogenous source of palmitate, the end product of DNL. Finally, SCD loss-of-function studies were employed to assess the importance of this enzyme to adipocyte function. Human preadipocytes were capable of differentiating to form adipocytes and expressed mRNA for the necessary enzymes for DNL. Glucose proved to be the main carbon contributor to de novo fatty acid synthesis, and glutamine was indentified as another source. Palmitate up-regulated DNL, with maximal up-regulation achieved with 50 μM, with a concomitant up-regulation of SCD. Interestingly, some subjects' adipocytes were unable to withstand a high (400 μM) concentration of palmitate showing signs of cell death. Palmitate-intolerant adipocytes had lower expression of SCD mRNA, less intracellular triacylglycerol and greater incorporation of [U-13C]palmitate in phospholipid fatty acids and consequently had a higher saturatedto- monounsaturated fatty acid ratio. Loss of SCD in adipocytes resulted in reduced cell membrane fluidity and reduced insulin sensitivity. In conclusion, DNL may not function to increase fat stores within adipocytes but may serve as a key regulator, acting in tandem with SCD to maintain cell membrane fluidity and insulin sensitivity within the human adipocyte.